Gummosis in Eucalypts - Bakshi, B. K. (Indian Forester, 1972)
Gummosis in eucalypts is due to injury to the cambium resulting in formation of kino ducts. The injury may be caused by physiogenic, pathogenic or biotic factors. Subsequent renewed cambial activity may result in the embedding of kino in the bark, in the 'boxes' and in the wood in 'gums' thus degrading wood quality in the latter case. Gummosis may be prevented by controlling all avoidable injuries to plants.